Tropomyosin and profilin cooperate to promote formin-mediated actin nucleation and drive yeast actin cable assembly - Alioto, Salvatore L. (Curr Biol, 2016)
Tropomyosins comprise a large family of actin binding proteins with critical roles in diverse actin-based processes [1], but our understanding of how they mechanistically contribute to actin filament dynamics has been limited. We addressed this question in S. cerevisiae, where tropomyosins (Tpm1 and Tpm2), profilin (Pfy1), and formins (Bni1 and Bnr1) are required for the assembly of an array of actin cables that facilitate polarized vesicle delivery and daughter cell growth. Formins drive cable formation by promoting actin nucleation and by accelerating actin filament elongation together with profilin [2]. In contrast, how tropomyosins contribute mechanistically to cable formation has been unclear, but genetic studies demonstrate that Tpm1 plays a more important role than Tpm2 [3, 4]. Here, we found that loss of TPM1 in strains lacking BNR1 but not BNI1 led to severe defects in cable formation, polarized secretion, and cell growth, suggesting TPM1 function is required for proper Bni1-mediated cable assembly. Further, in vitro TIRF microscopy demonstrated that Tpm1 strongly enhanced Bni1- but not Bnr1-mediated actin nucleation, without affecting filament elongation rate, whereas Tpm2 had no effects on Bni1 or Bnr1. Tpm1 stimulation of Bni1-mediated nucleation also required profilin and its interactions with both G-actin and formins. Together these results demonstrate that yeast Tpm1 works in concert with profilin to promote formin-dependent nucleation of actin cables, thus expanding our understanding of how specific tropomyosin isoforms influence actin dynamics.